Ecological risk and chemical speciation of heavy metals in surface sediments of the Pearl River Estuary for comprehensive assessment - Liu, Zhiyan; Wu, Qian; He, Chao; Zhang, Peng; Wang, Xiaoqin; Luo, Zifen; Yang, Liaoyuan; Huang, Chaoqing (Frontiers in Environmental Science, 2024)
The Pearl River Estuary, a vital ecological and economic zone in Southern China, has been heavily impacted by industrial discharges, leading to significant heavy metal contamination. To address the ecological implications of different chemical forms of heavy metals, this study systematically evaluated the total concentrations and chemical speciation of Cu, Zn, Cd, and Pb in surface sediments (0–2 cm) collected from 17 sites. Chemical speciation was determined using a modified BCR sequential extraction procedure, and pollution and ecological risks were assessed via the geo-accumulation index (Igeo), potential ecological risk index (RI), and risk assessment code (RAC). The results showed that all four metals exceeded background values, with Cd presenting the highest enrichment (39 times) and contributing 97% of the ecological risk. Speciation analysis revealed that Cd predominantly exists in bioavailable forms, posing severe ecological threats. This study highlights the urgent need for targeted remediation strategies to mitigate Cd contamination and its ecological impact on the estuary.